2016
DOI: 10.1016/j.jss.2016.06.056
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor responses are suppressed in trauma ICU patients

Abstract: Background Inflammation and activation of the innate immune system is often associated with traumatic injury and may involve alterations in Toll-like receptor (TLR)-mediated responses. Methods A prospective observational study was designed and conducted. Twenty-one severely injured (ISS = 16-41) trauma ICU patients and 6 healthy volunteers that served as controls were enrolled. Anticoagulated whole blood was collected at 2-12 days after ICU admission and incubated in the presence of media alone (baseline), z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Clinical studies attempting to evaluate TLR4-mediated inflammation via circulating markers usually employ ELISA quantitation of alarmins such as HMGB1, TLR4 mRNA expression in whole blood or mononuclear cell subsets, or mononuclear cell isolation and TLR4 activation ex vivo; increased TLR4 expression and ex vivo activation on a subset of mononuclear cells 24 to 48 hours after major abdominal surgery were proposed to predict systemic inflammatory syndrome (34). In contrast, ex vivo TLR4 activation of whole blood cell cultures was shown to be suppressed in trauma ICU patients (35). The measurement of the ability of plasma samples to activate TLR4 on a reporter cell line, which we employ for the first time in a clinical study, presents the advantage of representing the combined effect of agonists and antagonists of the receptor that may be present in the circulation at a given time point, and provides valuable information when used with the appropriate controls (control cells lacking the TLR4 activation in the presence of TLR4-independent NF-kB-inducing factors; ref.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies attempting to evaluate TLR4-mediated inflammation via circulating markers usually employ ELISA quantitation of alarmins such as HMGB1, TLR4 mRNA expression in whole blood or mononuclear cell subsets, or mononuclear cell isolation and TLR4 activation ex vivo; increased TLR4 expression and ex vivo activation on a subset of mononuclear cells 24 to 48 hours after major abdominal surgery were proposed to predict systemic inflammatory syndrome (34). In contrast, ex vivo TLR4 activation of whole blood cell cultures was shown to be suppressed in trauma ICU patients (35). The measurement of the ability of plasma samples to activate TLR4 on a reporter cell line, which we employ for the first time in a clinical study, presents the advantage of representing the combined effect of agonists and antagonists of the receptor that may be present in the circulation at a given time point, and provides valuable information when used with the appropriate controls (control cells lacking the TLR4 activation in the presence of TLR4-independent NF-kB-inducing factors; ref.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that neutrophil stimulation via TLR activation with various molecules leads to NET production. Further to this, the structure of the NETs is characteristic to the type of TLR stimulation [68]. TLR4 seems to be responsible for this kind of neutrophil activity in particular as many publications demonstrated their interaction via HMGB-1 [55], superoxide production [69], platelet activation [29] or IL-1β [70].…”
Section: Toll-like Receptorsmentioning
confidence: 99%